2016
DOI: 10.1111/ajo.12475
|View full text |Cite
|
Sign up to set email alerts
|

Implications of caesarean section for children's school achievement: A population‐based study

Abstract: Results: 162 women had a CS for failed induction (109, 67%) or labour arrest (53, 33%). Of the CS performed for failed induction , 106 (97%) did not meet the ACOG definition and of those performed for labour arrest 29 (55%) did not meet the ACOG definition. There were no statistically significant differences in cord artery lactate concentration, admission to special care nursery or blood loss with up to 24 hours of latent phase or >4 hours of labour arrest before decision for CS (p > 0.05). Conclusion: If we w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
0
14
2
Order By: Relevance
“…Another study of around 1200-3500 Australian children, depending on the outcome considered, reported no differences in child development at the age of 5 years and in school achievement at the age of 8 years between children born by actual VBAC compared with ERCS. 40 Compared with ERCS, our study only found a slight increase in the risk of any SENs and in certain types of SEN with actual VBAC, which might well be attributable to type-1 error or residual confounding. As we are not aware of any clinical reason to explain the reduced risk of language or speech disorder seen only with in-labour non-elective repeat caesarean, compared with ERCS, this finding might also be attributable to type-1 error or residual confounding.…”
Section: Discussioncontrasting
confidence: 61%
“…Another study of around 1200-3500 Australian children, depending on the outcome considered, reported no differences in child development at the age of 5 years and in school achievement at the age of 8 years between children born by actual VBAC compared with ERCS. 40 Compared with ERCS, our study only found a slight increase in the risk of any SENs and in certain types of SEN with actual VBAC, which might well be attributable to type-1 error or residual confounding. As we are not aware of any clinical reason to explain the reduced risk of language or speech disorder seen only with in-labour non-elective repeat caesarean, compared with ERCS, this finding might also be attributable to type-1 error or residual confounding.…”
Section: Discussioncontrasting
confidence: 61%
“…Some studies have revealed deficits in cognitive domains [20,21], delayed motor development [22,23], or a higher risk of mental health problems, such as autism and Attention-Deficit/Hyperactivity Disorder (ADHD) [24,25] in children who were born by CS. Some studies, though, found no effects of CS on child psychological outcomes [26][27][28][29] and some have reported positive outcomes [30,31]. These discrepancies might be due to different methodology, such as measurement of outcomes (e.g., parental report or direct child assessment), different sample characteristics, type of CS examined (planned for medical reasons or maternal request, emergency CS), or confounders that are controlled for.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, Smithers et al [ 9 ] analyzed the school assessment of children at the age of 8 years by comparing cesarean section ( n = 650) vs. vaginal birth ( n = 2959) in women with a previous cesarean delivery. The assessment included reading, writing, spelling, grammar, and numeracy.…”
Section: Introductionmentioning
confidence: 99%